The Effect of Giving Incentives and Work Discipline on Work Achievements that Impact on Employee Performance - Sri Mulyani (Universitas Negeri Makassar, 2021)
This study aims to determine the effect of incentives and work discipline on work performance which has an impact on employee performance at PT. Median Cipta Graha in Jakarta. The method used is explanatory research with a sample of 120 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study Incentives have a significant effect on work performance by 36.3%, hypothesis testing obtained a significance of 0.000 <0.05. Work discipline has a significant effect on work performance by 38.0%, hypothesis testing obtained a significance of 0.000 <0.05. Incentives and work discipline simultaneously have a significant effect on work performance by 51.9%, hypothesis testing is obtained a significance of 0.000 <0.05. Work achievement has a significant effect on employee performance by 39.7%, hypothesis testing obtained a significance of 0.000 <0.05.